Dynamic Farsighted Stability - Hannu Vartiainen (Aboa Centre for Economics (ACE), 2007)
We study farsighted stability under the assumption that coalitions may condition actions on the history of the play. vNM stable set over possible play paths is defined with respect to the indirect dominance relation. We show that such dynamic stable set always exists. It is characterized by a generalization of the ultimate uncovered set. In unbounded agenda setting context, the dynamic stable set implements only efficient outcomes if active coalitions form a majority.
Keywords: C71; C72; 330; vNM stable set; farsightedness; dynamic; agenda formation